2021
DOI: 10.1055/s-0041-1726411
|View full text |Cite
|
Sign up to set email alerts
|

Role of Minimally Invasive Surgery in Management of Penetrating Abdominal Trauma in Children

Abstract: Introduction Traditionally, exploratory laparotomy was used to treat penetrating abdominal trauma (PAT). At present, minimally invasive surgery (for diagnostic and therapeutic purposes) has developed and represents a rapidly evolving modality for dealing with PAT in stable children. In this article, we aim to present our experience, evaluate the effectiveness, and report the results of minimally invasive surgery (MIS) for PAT in stable pediatric patients. Materials and Methods This prospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Among the searched studies, 1314 were excluded because they examined other diseases ( n = 1129), were non-original research studies ( n = 48), did not include or had insufficient information ( n = 58), were written in a non-English language ( n = 19), or were duplicated ( n = 60). Finally, nine studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] examining 12,492 patients were included in the present meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the searched studies, 1314 were excluded because they examined other diseases ( n = 1129), were non-original research studies ( n = 48), did not include or had insufficient information ( n = 58), were written in a non-English language ( n = 19), or were duplicated ( n = 60). Finally, nine studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] examining 12,492 patients were included in the present meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted at children’s hospitals or pediatric trauma centers. Five studies were multicenter trials [ 20 , 22 , 23 , 25 , 27 ]. Evans et al [ 25 ] reported two cohorts derived from a single institution and NTDB; hence, we enrolled both institutional data and nationwide data independently in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations